سلاطین وامراء کو دعوت دین کے اسالیب اور عصر حاضر کے چیلینجز: تحقیقی مطالعہ: Preaching Islam to Rulers and Sultans in the Context of Contemporary Challenges: A Research-Based Study - Muhammad Nadeem Anwar,; Dr. Ghulam Haider, (Al-Amīr Research Journal for Islamic Studies, 2025)
This article explores the methods of inviting rulers and elites to Islam and their role in shaping an Islamic society. It begins by highlighting the significance of da‘wah, emphasizing that it is not merely a moral duty but a fundamental religious obligation. The Qur’an, Sunnah, and the Prophetic Seerah demonstrate that prophets consistently addressed leaders and rulers, recognizing their influence on society at large. The Prophet Muhammad ﷺ invited both tribal chiefs in Makkah and foreign rulers during the Madinan period through letters, dialogue, and diplomatic initiatives. The Rightly Guided Caliphs continued this mission with justice, tolerance, and wisdom. In the contemporary era, inviting rulers remains essential. Effective approaches include diplomatic engagement, intellectual dialogue, modern media, interfaith initiatives, humanitarian services, economic cooperation, and presenting Islam’s ethical values. Nonetheless, political, economic, intellectual, social, and global challenges persist. These can be addressed through patience, wisdom, and the strategic use of modern means. By doing so, rulers can be brought closer to Islam, paving the way for the establishment of a just and welfare-oriented Islamic society. Keywords: Da‘wah, Sultans and Rulers, Caliphs, Islamic Society, Prophetic Biography, Diplomacy, Dialogue, Contemporary Challenges.